2006
DOI: 10.2460/ajvr.67.5.837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on activation of the p38 mitogen-activated protein kinase pathway, c-Jun NH2 terminal kinase, and heat shock protein 27 in equine skeletal muscle

Abstract: The p38 pathway and JNK are activated in the vastus lateralis muscle after a single 20-minute bout of submaximal exercise in trained horses. Phosphorylation of HSP27 as detected in the study reported here is most likely induced through the p38 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(31 reference statements)
2
13
0
2
Order By: Relevance
“…Literature supports a differential response of these kinases after exercise, although most authors report transient activations following either resistance or endurance exercise (van Ginneken et al 2006;Kramer and Goodyear 2007). Our data support this differential activation state between p38 and ERK1/2.…”
Section: Discussionsupporting
confidence: 79%
“…Literature supports a differential response of these kinases after exercise, although most authors report transient activations following either resistance or endurance exercise (van Ginneken et al 2006;Kramer and Goodyear 2007). Our data support this differential activation state between p38 and ERK1/2.…”
Section: Discussionsupporting
confidence: 79%
“…Increased staining for phosphorylated HSP27 in biopsies from horses obtained within 10 min after apparently nondamaging aerobic exercise is reported by Von Ginneken et al (53). However, Koh and Escobedo (23) found Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Although the precise function of a majority of these induced proteins is still unclear, many Hsps, as molecular chaperones, provide cells with a mechanism to prevent damage caused by misfolded, damaged, aggregated proteins (Hightower 1991). Several studies have shown that earlier experience with the stressor helps to improve induction (Donnelly et al 1992;Marber et al 1993;Yellon et al 1992;Walker et al 1993;van Ginneken et al 2006), transfection (Suzuki et al 1997), or overexpression of Hsp proteins if the stressor occurs again (Marber et al 1995;Ooie et al 2005;Gauthaman et al 2005;Chiu et al 2003). It is known that Hsp induction, and particularly Hsp70, can protect the myocardium from ischemia and reduces the infarction size in mice (Wu and Tanguay 2006;Seok et al 2007).…”
Section: Discussionmentioning
confidence: 99%